THE DEVELOPMENT OF SCIENCE CPS (COLLABORATIVE PROBLEM SOLVING) LEARNING MODEL TO IMPROVE FUTURE ISLAMIC ELEMENTARY SCHOOL TEACHERS’ COLLABORATIVE PROBLEM-SOLVING SKILLS AND SCIENCE LITERACY - Putra, Miftakhul Ilmi S.; Widodo, Wahono; Jatmiko, Budi; Mundilarto, Mundilarto (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
The purpose of this ressearch is produce science learning material through guided inquiry model that valid, practical, and effective to increase collaborative problem solving skill and science literacy skill of student of Islamic primary school teachers. The development of learning material was tested in class student of Islamic primary school teachers 3rd semester Unipdu Jombang in academic year 2016/2017 since September - December 2016 with One group pretest-postets design. The data collection used observation method, test and quetionnaries. The data analysis techniqeus used descriptive analysis of quantitaive, qualitative and statistic non parametric. The result of this research are: 1) learning material developed has a valid category; 2) The practicality of learning material in terms of a good category in feasibility of lesson plans and the students activities in accordance with steps of CPS (Collaborative Problem Solving) model; and 3) the learning material effectiveness in terms of improving student learning achievement seen from the n-gain score with high category and improving Collaborative Problem Solving Skill and science literacy skill of student by getting the n gain score with high category and the student responds toward material and implementation of learning are very positive. It’s conclusion that the learning material through guided inquiry model are valid, practical, and effective to increase science literacy skill of student of Islamic primary school teachers.